Estimating the impact of changes in aggregate bank capital requirements on lending and growth during an upswing - Noss, Joseph; Toffano, Priscilla (Journal of Banking & Finance, 2016)
This paper estimates the effect of changes in banks’ capital requirements on lending by studying the joint dynamics of the historic aggregate capital ratio of the UK banking system and a set of macro-financial variables. This is achieved by means of sign restrictions that attempt to identify shocks in past data that match a set of assumed directional responses of other variables to future changes in capital requirements aimed at increasing the resilience of the banking system to losses during an upswing. This may provide policy-makers with a plausible ‘upper bound’ on the short-term effects of future increases in macroprudential capital requirements in certain states of the UK economic cycle. An increase in the aggregate bank capital requirement during an economic upswing is associated with a reduction in lending, with a larger effect on lending to corporates than on that to households. The impact on GDP growth is statistically insignificant.